Experimental Investigations And Study Corrosion Model Of Welded 6061 Aluminium Exposed In Marine Environment - Asmara, Y. P.; Siregar, J. P.; L. H., Shah; Tezara, C. (2014)
Existing methods to investigate preferential weld corrosion are dominated by empirical data. Such empirical models are limited in representing realistic corrosion mechanism which has segmented regions and individual of localised corrosion. Thus, it needs a concept that can interprete both each segmented regions and multi-reactions for self corrosion reaction and combinations of galvanic corrosion process. This research studied weld corrosion model occured on 6061 alumium that could be considered fundamental theories of electro-chemical process. The objective of this work is to construct corrosion model on weld aluminium using mechanistic theories to be fit with electrical circuit theories. The research studied corrosion process on two types of filler which are 4043 and 4047 weld filler. Studying electrochemical process involving corrosion mechanism have shown a realistic correlations. Model electro-chemical mechansim revealed that the HAZ region behaved as anode and shows higher corrosion rate on both filler. Electrical circuit model can also predicted galvanic effects on each part of weld regions to simulate both individual corrosion process and combination of galvanic corrosion. Sample with filler 4043 had higher corrosion rate compared to 4047 filler due to its inhomogeneous of microstructures.